2003
DOI: 10.1034/j.1600-0765.2003.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emdogain® on human periodontal fibroblasts in an in vitro wound‐healing model

Abstract: Therefore, EMD appears to exert an influence on cells that is compatible with improved wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 21 publications
5
58
2
Order By: Relevance
“…It has been shown that EMD has no effect on ALP activity (59); however, EMD both decreases (57) and increases (62,73,74) ALP activity in PDL fibroblasts. The production of osteopontin and osteoprotegerin has been shown to be increased by EMD (60,74). In addition, although EMD enhances bone-like nodule formation, it does not induce osteoblastic differentiation of PDL or gingival fibroblasts (23,55,59,62).…”
Section: Emdogain and Fibroblastsmentioning
confidence: 99%
“…It has been shown that EMD has no effect on ALP activity (59); however, EMD both decreases (57) and increases (62,73,74) ALP activity in PDL fibroblasts. The production of osteopontin and osteoprotegerin has been shown to be increased by EMD (60,74). In addition, although EMD enhances bone-like nodule formation, it does not induce osteoblastic differentiation of PDL or gingival fibroblasts (23,55,59,62).…”
Section: Emdogain and Fibroblastsmentioning
confidence: 99%
“…Recent clinical studies have demonstrated that the EMP matrix supports recolonization with mesenchymal cells [4]. In vitro, periodontal ligament cells derived from the mesenchyme, when cultured on EMP, increased their attachment rate, growth rate and metabolism, and subsequently released several growth factors and extracellular matrix (ECM) molecules including fibronectin at elevated levels into the medium [5][6][7][8][9][10][11]. Periodontal ligament cells have the ability to migrate, proliferate and differentiate into osteoblast-like and cementoblast-like cells, thereby promoting tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Gamal et al (12) observed significantly higher cell adherence in the healthy control group than in the periodontally-diseased treated control, suggesting that cultured human PDL fibroblasts prefer not to adhere to periodontally diseased treated root surfaces. Despite a number of reports on the role of EMD in periodontal regeneration (14,23,24), especially on PDL cells (8,14,20,28,38) and wound healing (31), different phenotypes of PDL fibroblasts can be isolated and may respond differently to regeneration attempts through biomimetics, which may explain the seemingly contradictory results in published studies regarding the in vitro effects of EMD (7). Chong et al (9) showed that EMD alone has a limited effect on PDL fibroblast proliferation.…”
Section: Resultsmentioning
confidence: 72%
“…Many in vitro studies have focused on the mechanism of action of EMD in periodontal ligament (PDL) cells during periodontal regeneration. In vitro studies demonstrate that EMD treatment of PDL fibroblasts stimulates proliferation, protein and collagen synthesis, and also induces mineralization (8,14,20,23,24,28,31,33,38).…”
Section: Introductionmentioning
confidence: 99%